Guidance note on stakeholder communication strategies for projects in South Asia. (Asian Development Bank, 2019)
The aim of this resource is to facilitate the meaningful participation of stakeholdersespecially civil society in ADB financed projects to help boost the social acceptability and impact of the banks operations. The note provides practical guidance on how to identify and map stakeholders and develop and deliver messages to them. It also provides a matrix for preparing a communications strategy and advice on its implementation and monitoring.